STRATEGI KOMUNIKASI PROGRAM PROMO AIR BERSIH PDAM TIRTA LAWU KARANGANYAR DALAM RANGKA MENINGKATKAN JUMLAH PELANGGAN - Darwanti, Lina; Perwita, Alvika Hening; Siswadi, Djoko Tri (KOMUNITAS, 2014)
This  Research  took  the  title  "  Strategy  of  Communication   for  Promo  Water  PDAM TIRTA LAWU Karanganyar Programme in order to Increase Number of  Customers " ( Study of Case of Clean Water Promo PDAM Karanganyar Unit Matesih Programme ) . This research was conducted in the PDAM Karanganyar office . In the  implementation of increasing the number of customers need  strategies  to plan and disseminateinformation with target to society . strategy of  communications  made  to  streamline  the  dissemination  activities  information  by  approaching directly , face to face and also media such as brochures . Strategy  implementation  are  used  to  disseminate  information  directly  to  society  .  this research aims to determine directly the task relationships in the subscription increase the number of customer PDAM TIRTA LAWU Karanganyar . The research method  used  descriptive qualitative  research is research which describes in detail by describing  all  the  problems  associated  with  what is  being  studied  that  is  about  strategy of communications  made  by  the  client  relationships  in  order  to  improve  number  of  customers. After  conducted  the  research  ,  it  can  be  concluded  that  in  the  dissemination of  information  in  order  to  attract  public  interest  required  communication  strategies  for  more streamline  activities  dissemination informations,  as  provide  a more  detailed explanation  of  the easy  in  obtaining  clean  water  by  using  the  services of  PDAM  .  subscription  required  on  the relationship delivery of information to the public  should be clear and easy to understand so that people can understand and not wrong to use the services of one of the PDAM.